2020
DOI: 10.1093/jhps/hnaa013
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral versus unilateral hip arthroscopy for femoroacetabular impingement: a systematic review

Abstract: One in four patients presenting with femoroacetabular impingement (FAI) has bilateral symptoms, and despite excellent outcomes reported after arthroscopic treatment of FAI, there remains a paucity of data on the outcomes following bilateral hip arthroscopy. This systematic review aims to examine the outcomes following bilateral (either ‘simultaneous’ or ‘staged’) versus unilateral hip arthroscopy for FAI. A systematic review of multiple electronic databases was conducted using the Preferred Reporting Items for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In a recent systematic review, the timing of the second procedure ranged from 3 weeks to 58 months (mean, 7.7 months), with favorable results seen regardless of the timing of the second procedure. 10 However, Kuhns et al demonstrated that patients who underwent the second operation before 10 months after the index hip had greater HOS-Activities of Daily Living and HOS-SSS scores as well as lower VAS pain scores when compared with patients who underwent the contralateral surgery after the 10-month period.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, the timing of the second procedure ranged from 3 weeks to 58 months (mean, 7.7 months), with favorable results seen regardless of the timing of the second procedure. 10 However, Kuhns et al demonstrated that patients who underwent the second operation before 10 months after the index hip had greater HOS-Activities of Daily Living and HOS-SSS scores as well as lower VAS pain scores when compared with patients who underwent the contralateral surgery after the 10-month period.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lower return to soccer rate among these players (68.8 vs. 78.2% for unilaterals), this difference did not reach statistical significance. Two recent systematic reviews [7, 12] reported on improved outcomes after a simultaneous or staged bilateral hip arthroscopy for FAIS, with similar efficacy and safety when compared with unilateral surgeries. These studies, however, did not focus on athletic populations and did not report on return to play after bilateral surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of radiological deformities does not always coincide with symptomatic FAI 3 , 4 . A common phenomenon is that most patients with FAI complain of unilateral hip pain only, and only a quarter of FAI patients have bilateral hips involved 5 . What causes the difference in symptoms of bilateral hips in patients with FAI has not been well‐studied.…”
Section: Introductionmentioning
confidence: 99%